The Role of Neurotransmitters in Relation to Psychiatric Conditions Throughout the COVID-19 Epidemic - Muhlisa, Safitri (HM Publisher, 2023)
Various studies have reported the presence of psychiatric symptoms among individuals diagnosed with COVID-19, encompassing heightened stress levels, impaired cognitive function, depressive mood, anxiousness, post-traumatic stress disorder (PTSD), psychotic symptoms, and suicidal ideation. The objective of this review was to elucidate the involvement of neurotransmitters in psychiatric disorders following the COVID-19 pandemic. There are multiple variables that can influence the results of research studies examining the presence of symptoms or the initiation of psychiatric disorders in individuals diagnosed with COVID-19. Factors associated with mental health difficulties include direct involvement in the healthcare field, presence of a psychiatric disease within the family, limited social support, advanced age, solitary living arrangements, and the utilization of high dosages of steroids during the acute phase. Multiple types of neurotransmitters are involved in the modulation of stress levels inside the human body. The neurotransmitters implicated in this process include dopamine, serotonin, epinephrine and norepinephrine, acetylcholine, gamma-aminobutyric acid (GABA), and glutamate. In summary, cytokines have a pivotal role in modulating the hypothalamic-pituitary-adrenal (HPA) axis within the brain, hence potentially giving rise to psychiatric manifestations including impaired sleep, heightened stress, depressive affect, and several other psychological disturbances.